Aortic aneurysm: An uncommon cause of dysphagia - Mujaheed Suleman; Jeremia Pyuza; Adnan Sadiq; Jay Lodhia (SAGE Open Medical Case Reports, 2022)
Dysphagia is a serious symptom and requires urgent investigations and prompt diagnosis to initiate appropriate therapy. Dysphagia aortica is a rare entity described as difficulty in swallowing due to external compression by the aorta. The incidence of this entity is unknown. Herein we present a 90-year-old woman who presented with a progressive 3-month history of dysphagia, diagnosed with aortic aneurysm who then developed related complications and succumbed. Dysphagia aortica should be considered in the list of differential diagnoses in a patient with dysphagia although rare. Early diagnosis and management are vital to avoid poor outcomes.